Photocatalysis studies using mesoporous modified V-MCM-48 Stober synthesis: acetaldehyde, carbon monoxide, ethanol, acetone, 2-propanol, & acetonitrile - Mahoney, Luther James (Kansas State University, 2010)
Although Degussia-Huls P-25 TiO[subscript]2 semiconductor photocatalyst has high photodegradation rate for organic molecules, it works only under ultra-violet (UV) light. Mesoporous metal doped V-MCM-48 silica was synthesized under ambient conditions for use as a visible-light photocatalyst to convert toxic probe molecules to innocuous products: CO[subscript]2 + H[subscript]2O. The synthesis employed a modified Stober metal doped MCM-48 silica method. Powder X-ray diffraction (XRD), diffuse-reflectance-ultra-violet-visible (DR-UV-vis) spectroscopy, and N[subscript]2 adsorption-desorpton analysis characterization methods were completed on V-MCM-48 mesoporous material. These characterization methods indicate V-MCM-48 structure had formed with visible light absorption and mesoporous properties. Photocatalysis studies were completed with V-MCM-48 under dark, visible, and UV-light illumination conditions for the following probe molecules: acetaldehyde, carbon monoxide, ethanol, acetone, 2-propanol, and acetonitrile. Acetaldehyde over V-MCM-48 was converted to CO[subscript]2 under dark, visible, and UV-light conditions. Carbon monoxide photooxidation occurred over V-MCM-48 under visible and UV-light. Ethanol and acetonitrile had smaller photodegradation activity over V-MCM-48. Acetone and 2-propanol had no activity photocatalytically. Under dark and visible light illumination, V-MCM-48 consumed approximately one-half acetaldehyde and produced one-third CO[subscript]2 concentration as compared with the P-25 TiO[subscript]2 under UV-light. V-MCM-48 produced two-thirds of the amount of CO[subscript]2 in comparison to nanoparticle Au/ZnO catalyst under UV-light. The results infer V-MCM-48 might be useful in gas and liquid phase photocatalysis including water-splitting due to a high oxidation state (V[superscript]5+), visible light absorption, and high surface area. In conclusion, an extended literature review has been completed and literature employed extensively throughout the thesis with potential methods to further the research on V-MCM-48/Si-MCM-48 in catalysis, chromatography, adsorption/gas separation, and solar collection/water-splitting.
Keywords: Gas-phase environmental remediation; Vanadium-Mobil-Composition of Matter-48 (V-MCM-48); Visible-light photocatalysis studies; Novel synthetic metal doped silica materials; Formation theories of zeolites; mesoporous materials; Chemistry, General (0485); Chemistry, Inorganic (0488); Chemistry, Physical (0494)